Physical Training Effects on Fitness Components in Young Athletes - Muhammad Rizky; Mohammad Fandi Kurnia; Herman Sayuti (Journal of Physical Education, Sport, and Human Performance, 2026)
Introduction. Physical fitness is a key indicator of adolescent health; however, training responses vary across fitness components and may be influenced by anthropometric factors such as body weight. This study aimed to analyze changes in physical fitness components following a 12-week functional training intervention and to examine the moderating role of body weight on training adaptations among female university students in Makassar. Methods. A pre–post intervention design was employed involving 14 purposively selected participants. The intervention consisted of structured functional training conducted three times per week (60 minutes/session), targeting six fitness components: core muscular endurance, upper-body muscular endurance, lumbar extension endurance, lower-body explosive power, static balance, and lateral agility. Data were analyzed using paired t-tests (α=0.05), Cohen’s d effect size, and Pearson correlation. Results. The results revealed a significant improvement only in core muscular endurance (p=0.0014; d=0.822), with a 30.2% increase, while other components showed no significant changes. Additionally, a significant negative correlation was found between body weight and improvements in lumbar extension endurance (r=-0.514; p=0.03). Conclusion. Core muscular endurance is the most responsive component to functional training, whereas body weight moderate adaptations in specific exercises. These findings highlight the importance of individualized training programs and provide a basis for developing region-specific fitness norms to support athlete monitoring in Indonesia.